Strategy and human resources management in non-profit organizations: Its interaction with open innovation - Márcio Oliveira; Marlene Sousa; Rui Silva; Tânia Cristina Sim\~oes de Matos dos Santos (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The socioeconomic changes that many countries have been experiencing in recent decades, caused by structural factors or by specific circumstances, where the pandemic crisis of COVID-19 is only the most recent example, have posed challenges to organizations, which present themselves more and more and in various forms as threatened by the possibility of fulfilling their mission. Public and private sectors increasingly present themselves as insufficient to respond effectively to day-to-day requests. This context of instability and the resulting impacts for non-profit organizations pose serious problems to the way in which governance is exercised and served as a motivation for carrying out a study that aimed to understand the influence of strategy and human resources on the governance of these organizations. A review of the literature on the variables under study made it possible to identify the sub-dimensions associated with each one of them and the respective indicators. Thus, for a quantitative study, it was possible to apply a questionnaire to 242 Holy Houses of Mercy in Portugal to understand the direct and indirect influences of strategic management and human resources management on the governance of these institutions. The results obtained show the existence of a positive relationship between the variables under analysis, confirming that not only do these variables influence, by themselves and directly, the governance of the institutions studied, but also the strategy influences human resources policies, which in turn have implications for the way the Holy Houses of Mercy deal with aspects associated with governance. It is concluded that, in general, for these organizations to be more effective in efforts to improve their governance processes, they must focus on strategic management and human resources management instruments.
Keywords: 650; governance; Holy Houses of Mercy; human resources management; non-profit organizations; strategy